(untitled) ("Journal "U". Economy. Management. Finance.", 2021)
In the current market relations, the profitability of an enterprise is the main criterion for evaluating the effectiveness of its financial and economic activities, which explains the relevance of this article. The article examines the role of profitability in the company’s activities, the main factors affecting its dynamics, and also considers the main indicators of profitability.